1962
DOI: 10.1017/s0022112062001160
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of the fluctuating pressure at the wall beneath a thick turbulent boundary layer

Abstract: Measurements of the turbulent pressure field at the wall beneath a thick (5-inch) turbulent boundary layer produced by natural transition on a smooth surface are reported. The data include the mean-square pressure, parallel to the stream, and spatial correlation of the pressure transverse to the stream.The root-mean-square wall pressure was 2.19 times the wall shear stress. The power spectra of the pressure were found to scale with the free-stream speed and the boundary-layer displacement thickness. A few test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
132
1
1

Year Published

1967
1967
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 372 publications
(163 citation statements)
references
References 9 publications
29
132
1
1
Order By: Relevance
“…2 The result <p2)qz/(r w) ~ 2.4 -+ 0.2 for the plane channel is in accordance with a large number of measurements [12]. This ratio is remarkably smaller at the inner wall of the annulus, however.…”
Section: Velocity and Pressure Fluctuationssupporting
confidence: 85%
See 1 more Smart Citation
“…2 The result <p2)qz/(r w) ~ 2.4 -+ 0.2 for the plane channel is in accordance with a large number of measurements [12]. This ratio is remarkably smaller at the inner wall of the annulus, however.…”
Section: Velocity and Pressure Fluctuationssupporting
confidence: 85%
“…7). Oscillations of the same order of magnitude have been found by Gorman [5] in an annulus (R2/R~ = 1.67) and even larger ones by Bakewell [13] for a pipe, but they did not appear in a boundary layer flow [12]. Hence, it must be concluded that these oscillations are strongly geometry-dependent and equations based on measurements for one specific geometry, such as those used by Reavis [4], are not sufficient.…”
Section: Pp(o ~ R)mentioning
confidence: 81%
“…The remains are the structures with a longer lifetime (lower frequency) that travel at a higher velocity at locations further away from the wall. The increase in the advection velocity with streamwise separation has also been observed by Willmarth & Wooldridge (1962) and Bull (1967) using arrays of pressure transducers. For two transducers of small streamwise separation (∼θ ), Willmarth & Wooldridge (1962) observed an advection velocity of 0.56U ∞ and Bull (1967) observed 0.53U ∞ while both estimated 0.83U ∞ for transducers of larger streamwise separation (∼8θ, beyond the measurement field of the current experiment) and attributed the trend to the decay of the high-frequency pressure fluctuations.…”
Section: Spatio-temporal Scales Of Happsmentioning
confidence: 52%
“…The broad range of pressure fluctuations within the turbulent boundary layer was initially classified into low-and high-frequency fluctuations by Willmarth & Wooldridge (1962). They conducted a comparison and associated the low-frequency fluctuations with a high advection velocity using space-time correlation of wall pressure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation